Larvicidal activity of some Curcuma and Kaempferia rhizome extracts against dengue fever mosquito Aedes aegypti Linnaeus (Diptera: Culicidae) - Md.Sukari, Mohd. Aspollah; Rashid, Nur Yuhasliza; Neoh, Bee Keat; Abu Bakar, Noor Haslizawati; Riyanto, Sugeng; Ee, Gwendoline Cheng Lian (Chemic Publishing Company, 2010)
Investigations were carried out to test the larvicidal activity of extracts of some Zingiberaceae plants species against the larvae of dengue fever mosquito Aedes aegypti. Fifteen crude extracts from three Curcuma species and two Kaempferia species were used for the test. Most of these plants were toxic to the mosquito larvae and indicated promising activity with LC50 values of less than 90 μg/mL. Among the five plants, hexane extract of Curcuma xanthorrhiza was the most toxic against Aedes aegypti with LC50 value of 26.4 mg/mL. - See more at: http://www.asianjournalofchemistry.co.in/user/journal/viewarticle.aspx?ArticleID=22_10_61#sthash.a5GblrYS.dpuf